Functional constipation in Chinese infants: disruptions in gut microbiota and urinary metabolome revealed by a cross-sectional analysis - Zhao, Haihong; Lu, Xiuxia; Lou, Hua; Ye, Yanbin; Ye, Hui; Li, Weiwei; Long, Ziyu; Zhang, Xuezhi; Wu, Jieling; Wang, Ji (Frontiers in Microbiology, 2025)
BackgroundFunctional constipation (FC) is regarded as the most prevalent functional gastrointestinal disorder among children and is closely related to the intestinal microbiota. Nevertheless, there is a paucity of data regarding this relationship in Chinese infants.MethodsIn this study, we investigated the alterations in gut microbiota of 79 FC infants under 2 years of age in China, using 31 balanced non-constipated (BC) children as controls. Some clinical parameters were evaluated, fecal microbiota was analyzed using 16S rRNA gene sequencing, and urinary metabolites were profiled via UPLC-Q-TOF/MS method.ResultsChildren with FC demonstrated significantly lower stool scale scores compared to BC group. Significant differences were observed in both microbial community composition and metabolite profiles between the FC and BC groups. The characteristic microbiota of the FC group included Prevotella, Alistipes, Collinsella and Eggerthella, associated with dietary fiber degradation, short-chain fatty acid and bile acid conversion, and participated in sphingolipid, thiamine, and glutathione metabolism. A combined biomarker exhibited excellent capacity in distinguishing FC from BC.ConclusionThis study offers new insights into the gut microbiota and metabolomic profiles associated with FC in young children, particularly that glutathione metabolism may be a new pathway for infant constipation, underscoring the potential for developing innovative therapeutic strategies through the integration of multi-omics approaches.